2008
DOI: 10.1002/jcc.21176
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism of palladium‐catalyzed silastannation of allenes by density functional theory

Abstract: The reaction mechanism of Pd(0)-catalyzed allenes silastannation reaction is investigated by the density functional method B3LYP. The overall reaction mechanism is examined. For the allene insertion step, the Pd-Si bond is preferred over the Pd-Sn bond. The electronic mechanism of the allene insertion into Pd-Si bond to form sigma-vinylpalladium (terminal-insertion) and sigma-allylpalladium (internal-insertion) insertion products is discussed in terms of the electron donation and back-donation. It is found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…128 Based on the theoretical studies on the Pd(0)-catalysed allene silaboration 125 and alkyne silastannation, 131 (Scheme 15). 132 The results suggested that the reaction pathway proceeds via (a) oxidative addition of Si-Sn to Pd(PH 3 ) 2 , (b) dissociation to form complex 89, (c) allene coordination and insertion into the Pd-Si bond, (d) isomerization from s-allyl 90 to p-allyl complex 91, and (e) reductive elimination to give the final product Z-93. The rate-determining step is the allene insertion into the Pd-Si bond.…”
Section: Addition Of Element-element To Allenesmentioning
confidence: 99%
“…128 Based on the theoretical studies on the Pd(0)-catalysed allene silaboration 125 and alkyne silastannation, 131 (Scheme 15). 132 The results suggested that the reaction pathway proceeds via (a) oxidative addition of Si-Sn to Pd(PH 3 ) 2 , (b) dissociation to form complex 89, (c) allene coordination and insertion into the Pd-Si bond, (d) isomerization from s-allyl 90 to p-allyl complex 91, and (e) reductive elimination to give the final product Z-93. The rate-determining step is the allene insertion into the Pd-Si bond.…”
Section: Addition Of Element-element To Allenesmentioning
confidence: 99%
“…Similarly, in a DFT study on Me–Me couplings a similar interaction was reported at the transmetalation TS . Support for the viability of such metal–metal-bonded bimetallic species is found in one particular example of an isolated complex with a Ni–Al bond, where X-ray data have revealed a structural arrangement with bridging methyl and oxy groups, which would actually be a model for a transmetalation event. , Perhaps not surprisingly, dinuclear complexes with metal–metal bonds have been shown to be active in catalysis. , …”
Section: Introductionmentioning
confidence: 99%
“…2), and reductive elimination can proceed through two pathways, i.e., monophosphine and bisphosphine pathway (Fig. 4), the reductive elimination prefers to proceed through the monophosphine pathway 3Ba?TS 34 ?4?6, similar to the palladium-catalyzed allenes bisselenation 48 and silastannation 60 reactions, in which the reductive elimination prefers the monophosphine pathway. In monophosphine pathway, the reductive elimination takes place directly through the transition state TS 34 to form complex 4.…”
Section: Reductive Eliminationmentioning
confidence: 83%
“…As transition state TS 56 is 1.9 kcal/mol higher than TS 34 (Fig. 4), the reductive elimination prefers to proceed through the monophosphine pathway 3Ba?TS 34 ?4?6, similar to the palladium-catalyzed allenes bisselenation 48 and silastannation 60 reactions, in which the reductive elimination prefers the monophosphine pathway.…”
Section: Reductive Eliminationmentioning
confidence: 83%
See 1 more Smart Citation